Daoist Knights Division in the Latin Kingdom of Jerusalem and Its Role in Protecting the Latin Christian Pilgrims to the Islamic East (493-583 AH / 110 0-1187 AD) - Ibrahim, Manar Ahmed Mohammad; Al-Qaaida, Abdul Hadi Nayef (Dirasat: Human and Social Sciences, 2025)
Objectives: This study highlights the Daoist Order of Knights in the Latin Kingdom of Jerusalem, explaining its role in protecting Latin pilgrims from Western Europe. It also examines its political and military influence in the Kingdom by tracing the circumstances surrounding its emergence and development, its founding charter, military organization, financial resources, and assessing its successes and failures. Methods: The study relies on a historical and analytical approach, examining documents related to the laws of Daoism, along with contemporary sources and historical studies related to the order. Results: The study concluded that the Daoist order, through its leaders, played a significant role in official councils and political missions in the Kingdom. It also participated in the battles the Kingdom of Jerusalem fought against the Muslims, particularly in its wars against Saladin, who succeeded in liberating Jerusalem and returning it to Islamic rule in 583 AH/1187 AD. Conclusions: The Daoist group of monks emerged as a military band that combined religious monasticism with the ideals of chivalry. It played a key role in protecting Latin pilgrims traveling to Jerusalem, receiving political, military, and economic support from the papacy. The order emerged as a feudal military class, participating in political events and official councils within the Latin Kingdom.